Effet de l’extrait d’ail ( Alium sativum.L) sur la croissance des bactéries lactiques(Streptococcus thermophilus et Lactobacillus bulgaricus) - BERKANE, Omar; TOUMI, Mohamed (My University, 2017)
Our study aims to determine the effect of garlic extracts (Allium sativum) on the physicochemical quality, microbiology of a fermented milk type yoghurt steamed during its fermentation at 45 ° C for 4 hours. The experiment was carried out with 0%, 4%, 6%, 8% extract incorporation rates in the steamed fermented milks, respectively. Each parameter studied is represented by 4 pots of 100 ml; Or an overall number of 12 experimental samples. During the 4 hours of fermentation, the following measurements and controls were carried out each hour on each processed product: Dornic acidity, pH. It appears during the fermentation and post-acidification period that the measured acidity values are non-proportional with the increased content of garlic added during the preparation of the fermented milks. This tendency is reversed for the pH, which shows slight decreases with the increase in the level of garlic in the products. Moreover, the number of specific germs of yogurt, namely Streptococcus thermophilus and Lactobacillus bulgaricus, does not meet the standards required for steamed yoghurt; 107 live germs / ml.We tasted our finished products and we did not detect any taste or aroma of the garlic.
Keywords: Ail; bactéries lactiques; lait fermentés; Steamed yoghurt; fermented milk; Garlic (Alium sativum.L).